Hope and climate-change engagement from a psychological perspective. (February 2023) - Ojala, Maria
Abstract: This article reviews recent research about climate-change hope and engagement. Cognitive climate-change hope is consistently positively related to engagement, while the results are less consistent regarding hope as an emotion. It is argued that when conducting research about hope as an emotion sources of hope need to be considered, since they can be both constructive and less constructive seen from a climate-change engagement perspective. Additionally, collective climate-change action can lead to constructive hope. The conclusion is that in future research there is a need to go beyond the dichotomy between cognition and emotion and in interventions to go beyond optimistic messages and take into account preconditions for constructive hope.